Comprehensive Analysis of Physico-Chemical Characteristics of Ground Water Quality in the Vicinity of Sugarmills, Meerut District, UP - Mrs Sujata Malik; Prof. (Dr) Seema; Dr. Yashovardhan (International Journal of Scientific Research in Science and Technology, 2025)
Sugar mill is considered as one of the most polluting industries around the globe. They use huge fresh water during various processing activities and discharge the waste water having various contaminations into nearby water resources. Ground water nearby sugar mills is assumed to be unfit to drink with high risk when polluted waste water ie effluents from sugar industries is discharged untreated. So, the physico-chemical profile of groundwater nearby area of two sugar mills A and B (Daurala Sugar mill named as A and Bajaj Hindustan Sugar Industry Ltd named as B) in Meerut district UP at three seasonal periods (November, January and April) during 2023-24 was determined. Color, temperature, pH, DO, BOD, COD, Chloride, TS, TDS TSS, Sulphate, Oil and grease, Fluoride have been determined for both sugar mills. The ground water samples were compared with the prescribed limit of ground water given by BIS. Results of this endeavors indicate that mostly parameters were observed and found within the permissible limit and a few exceed. This suggests that continuously monitoring by government agencies and public awareness may play a vital role in managing the ground water quality.
Keywords: Sugar Mill; Waste-Water; Effluent; Ground Water; Physico-Chemical Parameters